Green Illusions: Governing CSR Aesthetics - Richardson, Benjamin J. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
This article makes a novel argument that governance of corporate environmental activities should recognize that the business corporation is an aesthetic phenomenon, including the environmental practices and communications undertaken in the name of “corporate social responsibility” [CSR]. Corporate identities and CSR practices are aesthetically projected through logos, trademarks, websites, the presentation of products and services, stylish offices, company uniforms, and other aesthetic artefacts. This corporate “branding” dovetails with the broader aestheticization of our pervasive media and consumer culture. Aesthetics has particular salience in CSR for influencing, and sometimes misleading, public opinion about corporate environmental performance. Consequently, in disciplining unscrupulous corporate behaviour, governance methods must be more responsive to such aesthetic characteristics. The green illusions of business communications create difficulties for regulation, which is better suited to disciplining discrete misleading statements about retailed products or trademarks rather than tackling the broader aesthetic character of business and the marketplace. The article suggests that non-state actors who are more sensitive to aesthetics can help to fill some of this governance void. The “counter-aesthetic” strategies of social and environmental activist groups can inject a subversive narrative that can help to unmask these green illusions. Although the history of such tactics suggests they probably have only a modest effect in challenging corporate deception, the law can assist by protecting public spaces from corporate marketing and sponsorship.